2021
DOI: 10.22541/au.161674688.85580897/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CanVaS: Documenting the genetic variation spectrum of Greek cancer patients

Abstract: National genetic variation registries vastly increase the level of detail for the relevant population, while directly affecting patient management. Herein, we report CanVaS, a Cancer Variation reSource aiming to document the genetic variation of cancer patients in Greece. CanVaS comprises germline genetic data from 7,363 Greek individuals with a personal and/or family history of malignancy. The dataset incorporates ~24,000 functionally annotated rare variants in 97 established or suspected cancer susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Overall, this approach empowers subpopulation analysis, study of Greek population isolates, and investigation of possible founder effects. The strong founder effects observed in Greek subpopulations has been recently highlighted in a genetic analysis performed in Cretan isolates, where it was shown that three pathogenic variants in BRCA1 andBRCA2 , unique to the Cretan subpopulation, namely NM -007294.3:c.5492del in BRCA1 and NM 000059.3:c.7806-2A>T and NM 000059.3:c.6842-2675 7008-5558del, both in BRCA2, account for 48% of identified PVs in BRCA1 and BRCA2 among breast and ovarian cancer patients of Cretan descent (Apostolou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, this approach empowers subpopulation analysis, study of Greek population isolates, and investigation of possible founder effects. The strong founder effects observed in Greek subpopulations has been recently highlighted in a genetic analysis performed in Cretan isolates, where it was shown that three pathogenic variants in BRCA1 andBRCA2 , unique to the Cretan subpopulation, namely NM -007294.3:c.5492del in BRCA1 and NM 000059.3:c.7806-2A>T and NM 000059.3:c.6842-2675 7008-5558del, both in BRCA2, account for 48% of identified PVs in BRCA1 and BRCA2 among breast and ovarian cancer patients of Cretan descent (Apostolou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing was performed on patients' DNA, using either Sanger sequencing, Next Generation Sequencing (NGS)-implemented multigene panel or Multiplex Ligation-dependent Probe Amplification (MLPA) as previously described (Fostira et al, 2020). More specifically, individuals referred for genetic testing between 1999-2012 were tested through Sanger sequencing exclusively.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation